Mesorectal Lymph Node Metastases as Index Lesion in 68Ga-PSMA-PET/CT Imaging for Recurrent Prostate Cancer - Leitsmann, Conrad; Schmid, Marianne; Sahlmann, Carsten-Oliver; Trojan, Lutz; Strauss, Arne (Frontiers in Surgery, 2021)
Purpose: Several studies have demonstrated an advantage of 68Ga-PSMA-PET/CT as staging modality for detection of prostate cancer (PCa) metastases. Data concerning metastatic manifestation and impact on PCa development of mesorectal lymph nodes (MLN) is limited. Our investigation describes MLN metastases as index lesion in 68Ga-PSMA PET/CT imaging for recurrent PCa. Methods: Twelve PCa patients with biochemical recurrence (BCR) after primary therapy who prospectively underwent a baseline 68Ga-PSMA-PET/CT initially showed MLN metastases. Eight of these patients received a follow-up 68Ga-PSMA-PET/CT to evaluate treatment response and further evolution. Prostate-specific antigen (PSA)-levels, changes in PSMA-uptake of MLN metastases and further 68Ga-PSMA PET/CT findings were recorded. Results: Median PSA at the first 68Ga-PSMA-PET/CT was 5.39 ng/ml. In all patients therapeutic management changed after the first 68Ga-PSMA-PET/CT. Androgen deprivation therapy (ADT) was initiated in seven of eight patients, one patient restarted initial ADT. Three patients additionally received salvage radiation therapy (sRT) including the prostatic lodge and docetaxel chemotherapy was started in one case. At follow-up, a decrease of PSA-level was detected in all patients (median 2.05 ng/ml) after median 10 months. In six of eight patients we observed a decrease or complete regress of PSMA-uptake in MLN in the follow-up 68Ga-PSMA-PET/CT. Conclusion: MLN metastases detected by 68Ga-PSMA-PET/CT seem to be a relevant localization of tumor manifestation and may serve as index lesion in the treatment of recurrent PCa. Besides the known oncological benefits of ADT and sRT, in case of sole MLN metastases individualized therapy like salvage lymphadenectomy or RT with a defined radiation field could be options for these patients.